The validity and reliability of the my jump lab app for the measurement of vertical jump performance using artificial intelligence - Balsalobre-Fernández, C.; Varela-Olalla, D. (Sensors, 2024)
The countermovement jump (CMJ) is a widely used test to assess lower body neuromuscular performance. This study aims to analyze the validity and reliability of an iOS application using artificial intelligence to measure CMJ height, force, velocity, and power in unloaded and loaded conditions. Twelve physically active participants performed 12 CMJs with external loads ranging from 0% to 70% of their body mass while being simultaneously monitored with a pair of force platforms and the My Jump Lab application. The scores for jump height, mean propulsive force, velocity, and power between devices were compared for validity and reliability purposes. The force platform and the application showed a high association (r > 0.91, p < 0.05) for measuring CMJ height, force, velocity, and power. Small and no statistically significant differences (p < 0.05) were observed in most loading conditions. Both instruments showed high reliability (Cronbach`s a > 0.93, Coefficient of variation < 6%) for measuring the different trials performed by each participant. The My Jump Lab application was shown to be valid and reliable for measuring CMJ height, force, velocity, and power in both loaded and unloaded jumps, eliminating the problems associated with the cost and portability of force plates for daily practice.